Bladder wall abscess revealing squamous cell carcinoma in an adult with neurogenic bladder: A rare case report - Viktoriya Boncheva-Henderson; Katie Mallalieu; Omid Yassaie (Urology Case Reports)
Bladder wall abscesses are rare and present a diagnostic challenge, particularly in high-risk patients. We report the first known case of a bladder wall abscess in an adult female with a neurogenic bladder using clean intermittent self-catheterisation (CISC), ultimately diagnosed with squamous cell carcinoma (SCC) of the bladder. Infective symptoms and imaging consistent with abscess delayed the diagnosis of moderately differentiated SCC. This case highlights the diagnostic difficulty of bladder abscesses and the importance of early histological evaluation in atypical or non-resolving lesions. Malignancy should always be considered in high-risk individuals with neurogenic bladder and long-term CISC.